ANALISIS PENGELOLAAN ARSIP DINAMIS AKTIF LAPORAN HASIL PEMERIKSAAN PADA INSPEKTORAT PROVINSI JAWA TENGAH - Andhika, Rifky Fajar; Widyanti, Dika Vivi (Bangun Rekaprima, 2023)
There is an intensity to the observation of this research to understand the management of the active dynamic archive of the Examination Results Report (LHP) at the Central Java Provincial Inspectorate and also the obstacles and solutions to such obstacles. As for the observations, the research is qualitatively descriptive and uses a method of data collection, documentation, and interviews. Observations show that LHP archive processing includes creation, maintenance, storage, and shrinkage. Creation processes include creation in the processing unit, recording in the archive unit, and scanning. LHP archives are stored in the archive unit room and also in the record center using a number storage system. The process of LHP shrinkage has not been completed. The obstacles faced are the lack of SDM, lack of storage space, insufficient security aspects of the record center, and also poor archival systems, according to Agus Sugiarto and Teguh Wahyono. The advice that can be given is to: 1) make the recruitment of archive experts; 2) repair the corrupted record center; 3) make the procurement of archive equipment; 4) improve the security aspects of the record center; and 5) make the process of narrowing strictly.